Influence of abutment material on peri-implant clinical parameters: a prospective study - Fabiano Cortez Zanardo; José Della Pasqua Neto; Luiz Henrique Alves Madeira; Jamil Awad Shibli; Keize Távora Barbosa; José Augusto Rodrigues; Alessandra Cassoni (Brazilian Dental Science)
Objective: This study evaluated the peri-implant clinical parameters of zirconia versus metallic abutments for standardized custom-made implantsupported single-tooth restorations. Material and Methods: Sixteen subjects received 30 dental implants on esthetic region of upper jaws. Test group had 14 implant-supported single-tooth restorations with ceramic abutment and control group had 16 restorations with metallic abutment. Peri-implant clinical parameters were recorded after 110 ± 10 days in function at six sites by each implant, in each subject. The means of clinical measures: probing depth (PD) and clinical attachment level (CAL); mean of percentages of sites with visible plaque (VP), bleeding on probing (BOP) and suppuration (SU) were recorded to each subject. To verify differences between groups Mann Whitney U-test was selected PD and CAL and k-light test VP, BOP and SU. Results: One zirconia implant-supported single-tooth restoration fractured at insertion time. The mean of PD, CAL, and BOP of the samples sites were lower to test group than control (p < 0.05). There were no differences of mean levels of VP and S between test and control group (p > 0.05). Conclusion: Clinical parameters around implant-supported restorations were influenced by abutment type with better results to zirconia abutments, at least, after short time period evaluation.